2022
DOI: 10.1021/acsomega.2c00773
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed C–H Borylation of CF3-Substituted Pyridines

Abstract: Iridium-catalyzed C–H borylation of CF 3 -substituted pyridines is described in this paper. The boronic ester group can be installed on the α, β, or γ position of pyridine by an appropriate substitution pattern. Sterically governed regioselectivity provides convenient access to a variety of CF 3 -substituted pyridylboronic esters. These catalytic C–H borylation reactions were carried out neatly without the use of any solvent. Several functional groups, such as halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Some reported metal complexes of chalcones also exhibit antihyperglycemic and antimicrobial activities [29,30] . The electrochemical properties of various chalcones have been demonstrated using a three‐electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte [31–33] . In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones [34] .…”
Section: Introductionmentioning
confidence: 99%
“…Some reported metal complexes of chalcones also exhibit antihyperglycemic and antimicrobial activities [29,30] . The electrochemical properties of various chalcones have been demonstrated using a three‐electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte [31–33] . In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones [34] .…”
Section: Introductionmentioning
confidence: 99%